A new feather mite species of the genus Proctophyllodes Robin, 1877 (Astigmata: Proctophyllodidae) from the Long-tailed Tit Aegithalos caudatus (Passeriformes: Aegithalidae)—morphological description with DNA barcode data - Mironov, Sergey V.; Dabert, Jacek; Dabert, Miroslawa (Zootaxa, 2012)
A new feather mites species, Proctophyllodes valchukae sp. n., is described from the Long-tailed Tit, Aegithalos caudatus(Linnaeus, 1758) (Passeriformes: Aegithalidae), captured in the Primoriye (Russian Far East). The new species belongsto the tricetratus species group and is most closely related to P. stachyris Atyeo et Braasch, 1966. For the first time forfeather mites the standard morphological description is supplemented by sequence data of the mitochondrial cytochrome c oxidase subunit I gene fragment (COI) and nuclear D2 region of 28S rDNA.